2008
DOI: 10.1177/1753193408094156
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Responsiveness and Construct Validity of the Spanish Version of the Dash Instrument for Outcomes Assessment in Open Carpal Tunnel Release

Abstract: The objective of this study was to evaluate the responsiveness and construct validity of the Spanish version of the DASH as outcome measure for carpal tunnel surgery. The study population was 42 patients with the diagnosis of carpal tunnel syndrome (CTS) based on clinical and electrophysiological criteria. The clinical design was a classic Cohort study with measures the day before and 12 weeks after open carpal tunnel release. The Spanish version of the DASH was compared to the physical exam measures as dexter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
0
13
0
11
Order By: Relevance
“…Studies have found that the Japanese version of DASH had a small degree of responsiveness and the Spanish version of DASH had a moderate degree of responsiveness in terms of the SRM and ES for the patients with CTS (Table 3). 21,22) Compared with these studies, the K-DASH was found to have a larger degree of responsiveness (SRM, 0.8; ES, 0.8) for Korean patients with CTS. The reason that the K-DASH had a larger responsiveness is not clear.…”
Section: Discussionmentioning
confidence: 79%
“…Studies have found that the Japanese version of DASH had a small degree of responsiveness and the Spanish version of DASH had a moderate degree of responsiveness in terms of the SRM and ES for the patients with CTS (Table 3). 21,22) Compared with these studies, the K-DASH was found to have a larger degree of responsiveness (SRM, 0.8; ES, 0.8) for Korean patients with CTS. The reason that the K-DASH had a larger responsiveness is not clear.…”
Section: Discussionmentioning
confidence: 79%
“…The validation studies into Spanish show great validity in their construction with a great sensibility to change in pain [26] . The study of Gay et al even advised to have the DASH performed as a single test, in a study at 6 and 12 weeks of evaluation [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Todas las versiones españolas de los instrumentos de medición de resultados empleados presentaban un nivel satisfactorio de confiabilidad (consistencia interna y reproductibilidad), así como validez para medir resultados en una población de pacientes afectos de neuropatía compresiva. [52][53][54] Análisis Estadístico. Valoración de resultados.…”
Section: Tratamientounclassified
“…Así, existe una mejoría de los síntomas en relación a la compresión distal en una magnitud muy similar a la reportada en la población de STC por otros autores. [54][55][56][57][58][59] En cambio, la magnitud de la mejoría observada con el instrumento DASH fue menor a la que se observa en aquellos pacientes afectos de STC. 49,56 Ello se debe a que el instrumento DASH es específico de MMSS y diseñado para medir discapacidad de MMSS; y por tanto, es capaz de detectar detrimentos de la salud que son ocasionados por la compresión proximal.…”
Section: Tratamientounclassified